ANALYSIS THE IMPLEMENTATION OF PROJECT-BASED LEARNING (PJBL) BASED ON DIGITAL APPLICATIONS IN BIOLOGY GRADE 10 VIRUS LEARNING AT SMAN 1 KLAPANUNGGAL - Eka Ratna Safitri; Esti Ichtiarni; Dita Halleyna; Diah Fitriani; Aini Setiawati; Supardi (International Journal of Cultural and Social Science, 2025)
Education in the 21st century requires the implementation of student-centered learning models that are capable of developing 4Cs (Critical thinking, Creativity, Collaboration, and Communication). One learning model that is relevant to these demands is Project-Based Learning (PjBL) especially when integrated with the use of digital applications. This study aims to analyze: (1) the effectiveness of implementing PjBL based on digital applications, and (2) the challenges of PjBL learning based on digital applications. This study uses a qualitative approach with a triangulation method. The research sample was 70 students enrolled in class X of SMAN 1 Klapanunggal. Data were analuzed using the interactive model of Miled and Huberman with four stages. The research findings show that: (1) the implementation of PjBL based on digital applications in learning class X Biology virus material at SMAN 1 Klapanunggal shows a good level of effectiveness, marked by increased student activity, increased understanding of the concept of virus material, development of collaboration and communication skills, and good student responses to learning, and (2) there are various challenges that arise, including differences in students’ digital literacy abilities, limited learning time, technical constraints and infrastructure, and group work management.